A Novel Antihepatitis Drug, Bicyclol, Prevents Liver Carcinogenesis in Diethylnitrosamine-Initiated and Phenobarbital-Promoted Mice Tumor Model. (21st February 2012) - Sun, Hua; Yu, Linghong; Wei, Huailing; Liu, Gengtao
Abstract : Bicyclol, an antihepatitis drug developed by Chinese scientists, has been shown to prevent the malignant transformation induced by 3-methylcholanthrene and 12- O -tetradecanoylphorbol-13-acetate in WB-F344 rat liver epithelial cells. This study provides further evidence on its role as a chemopreventive agent in experimental mice with diethylnitrosamine- (DEN-) initiated and phenobarbital- (PB-) promoted liver carcinoma. Liver tissue and serum were collected. In the two-stage model of hepatocarcinogenesis in mice, oral administration of bicyclol (100, 200 mg/kg) before DEN injection showed significant reduction in the incidence of hepatocellular foci, nodules, or carcinoma. Histopathological examination revealed that there was no hepatocellular carcinoma (HCC) and hepatoma formation in the mice pretreated with bicyclol (200 mg/kg) at week 20, while the mice treated with DEN/PB developed 33.3% HCC and 55.6% hepatoma. Furthermore, the serum levels of alanine aminotransferase (ALT), alkaline phosphatase (ALP), and α -fetal protein (AFP) in serum significantly increased in the DEN/PB model group in comparison with the control group. Pretreatment with bicyclol showed a marked reduction in the above condition. Bicyclol also decreased the expression of AFP and proliferating cell nuclear antigen level in the liver tissue and attenuated the decrease in body weight. In this study, we also found that 10 weeks after stopping the administration of PB and drugs, the control and bicyclol-treated (200 mg/kg) animals showed no HCC and hepatoma formation at the time of termination whereas DEN/PB-induced mice developed 100% hepatoma and 50% HCC. These results further indicate that bicyclol has the chemopreventive potential for liver carcinogenesis induced by carcinogens.